Alzheimer's Disease: Microenvironment Remodeling Micelles for Alzheimer's Disease Therapy by Early Modulation of Activated Microglia (Adv. Sci. 4/2019). Issue 4 (20th February 2019) - Lu, Yifei; Guo, Zhongyuan; Zhang, Yujie; Li, Chao; Zhang, Yu; Guo, Qin; Chen, Qinjun; Chen, Xinli; He, Xi; Liu, Lisha; Ruan, Chunhui; Sun, Tao; et al.
Abstract : An Alzheimer's disease (AD) brain is featured with the oxidative and inflammatory microenvironment caused by overactivated microglia. In article number1801586, Chen Jiang and co‐workers design a brain normalizing system to eliminate reactive oxygen species (ROS) and reeducate microglia from an early phase of AD. Through its efficient neuroprotection and microglia modulatory functions, decreased Aβ plaque burdens and improved cognition are achieved.